PENGARUH METODE PENGERINGAN TERHADAP KADAR VITAMIN C DAN AKTIVITAS ANTIOKSIDAN DAUN KELOR (Moringa oleifera) - Paramita, Vilia Darma (Jurnal Agritechno, 2023)
Moringa oleifera leaves are rich in nutrients because they contain protein, carbohydrates, fats, fiber, vitamins and minerals, are widely used as food and medicine. This study aimed to determine the effect of various drying methods on vitamin C levels and antioxidant activity of Moringa leaves. This study compared the levels of vitamin C and antioxidant activity of moringa leaves dried by sun drying method, indoors and oven at 40, 50 and 60oC. The results showed that the best drying was using an oven at 40oC and the sun with vitamin C levels of 15.82 and 15.04 mg/100 g of material, respectively. In general, various drying methods did not affect antioxidant activity as indicated by the IC50 value which was classified as a strong antioxidant, but for treatment with high temperatures (50 and 60oC) there was a slight decrease in the IC50 value from the IC50 value of fresh leaves, this might be due to the production of Maillard reaction products. (MRPs) which are antioxidants. Research showed that the oven drying method at 40°C gives the best result.